Misuse of Antibiotics in COVID-19 Era - Aslam, Muniba; Dodani, Sunil Kumar; Naseem, Asma (Infectious Diseases Journal of Pakistan, 2022)
The emergence of SARS-COV-2 pandemic in late December 2019 has taken the health care community around the world by storm. The race to medical breakthroughs for COVID treatment has shifted focus from other public health concerns that were at the forefront in the pre-COVID era. Among these are the alarming developments in antimicrobial resistance; a crisis in its own right which Larry Kerr, co-chair of the transatlantic task force on antimicrobial resistance describes as ‘a multitude of small fires that are much less visible than the single massive firestorm that is the covid-19 pandemic. The first wave of the pandemic marked by diagnostic limitations and uncertainty about the pathophysiological nature of the virus saw a gigantic upsurge in the indiscriminate use of broadspectrum antibiotics that has not declined even as we approach the end of a year. The scarcity of sufficient data detailing antibiotic prescription to Covid patients during the pandemic masks the probable long-term consequences of this lapse in antibiotic stewardship.